Предмет: Алгебра,
автор: DiKiY444
Тема: Куб суммы и куб разности двух выражений
Представьте выражение в виде многочлена.
(х+у)^{3}
(p+q)^{3}
(2+a)^{3}
(x-2)^{3}
(a+2b)^{3}
Ответы
Автор ответа:
0
(х+у)^{3} = х³+3х²у+3ху²+у³
(p+q)^{3} = p³+3p²q+3pq²+q³
(2+a)^{3} = 8+12a+6a+a³ = 8+18a+a³
(x-2)^{3} = x³-6x²+12x-8
(a+2b)^{3} = a³+6a²b+12ab²+8b³
(p+q)^{3} = p³+3p²q+3pq²+q³
(2+a)^{3} = 8+12a+6a+a³ = 8+18a+a³
(x-2)^{3} = x³-6x²+12x-8
(a+2b)^{3} = a³+6a²b+12ab²+8b³
Похожие вопросы
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Психология,
автор: unicornbestie
Предмет: Математика,
автор: matuhinandrei19
Предмет: Химия,
автор: kir01com
Предмет: Математика,
автор: Машкаmash